A Complex Intervention for Alcohol Misuse Among Conflict-Affected Populations in Uganda and Ukraine: Study Protocol for the Qualitative Components in the CHANGE Trial. (13th December 2021) - Massazza, Alessandro; Fuhr, Daniela C.; Bogdanov, Sergiy; Tol, Wietse A.; Roberts, Bayard; Nadkarni, Abhijit; Akudrabo, Geoffrey; Skovgaard Andersen, Lena; Dumchev, Kostyantyn; Karachevskyy, Andriy; Kinyanda, Eugene; Koss, Kateryna; et al.
Qualitative research is increasingly being integrated within the development and evaluation phases of trials of complex health interventions. Qualitative research can complement effectiveness data and provide insights around how context and implementation impact the results of the trial and to what extent interventions fit implementation contexts after evaluation. Several qualitative studies have been conducted at different stages of trials of mental health and psychosocial support interventions for populations affected by adversity such as armed conflict and disasters. However, these qualitative components are usually implemented as disjointed components within the trial. The current protocol aims to provide a shared framework detailing the qualitative components of the CHANGE project trial: a program of work to address alcohol misuse and associated mental health comorbidities among conflict-affected populations in Uganda and Ukraine. In particular, the objectives of the current protocol are (i) to identify the specific qualitative questions and methods that will be undertaken in CHANGE; (ii) characterize the different methodological approaches to analyzing the data; and (iii) explain how each qualitative component within the different work-packages will cumulatively add value to each other over the duration of the CHANGE project. The current protocol will represent a useful template for the integration of serial qualitative research components within complex health interventions in humanitarian settings. Each qualitative components described will undergo formal ethics approval by ethics boards in the United Kingdom, Uganda, and Ukraine. Multiple mechanisms will be in place to ensure rigor and trustworthiness of the research by meeting the criteria of credibility, transferability, dependability, and confirmability.